SWIP—a stabilized window for intravital imaging of the murine pancreas. Issue 6 (15th June 2022) - Du, Wei; Adkisson, Christian; Ye, Xianjun; Duran, Camille L.; Chellakkan Selvanesan, Benson; Gravekamp, Claudia; Oktay, Maja H.; McAuliffe, John C.; Condeelis, John S.; Panarelli, Nicole C.; Norgard, Robert J.; Sela, Yogev; et al.
Abstract : Abstract : Pancreatitis and pancreatic ductal adenocarcinoma (PDAC) are grave illnesses with high levels of morbidity and mortality. Intravital imaging (IVI) is a powerful technique for visualizing physiological processes in both health and disease. However, the application of IVI to the murine pancreas presents significant challenges, as it is a deep, compliant, visceral organ that is difficult to access, easily damaged and susceptible to motion artefacts. Existing imaging windows for stabilizing the pancreas during IVI have unfortunately shown poor stability for time-lapsed imaging on the minutes to hours scale, or are unable to accommodate both the healthy and tumour-bearing pancreata. To address these issues, we developed an improved stabilized window for intravital imaging of the pancreas (SWIP), which can be applied to not only the healthy pancreas but also to solid tumours like PDAC. Here, we validate the SWIP and use it to visualize a variety of processes for the first time, including (1) single-cell dynamics within the healthy pancreas, (2) transformation from healthy pancreas to acute pancreatitis induced by cerulein, and (3) the physiology of PDAC in both autochthonous and orthotopically injected models. SWIP can not only improve the imaging stability but also expand the application of IVI in both benign and malignant pancreas diseases.